2020
DOI: 10.1155/2020/8864218
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Adrenal Mass Presents as Proximal Epithelioid Sarcoma

Abstract: Epithelioid sarcoma (ES) is a rare malignant mesenchymal neoplasm that accounts for less than one percent of all soft-tissue sarcomas. Only two cases of ES involving the adrenal gland were found after a literature review. We report a case of an 82-year-old female initially presenting with right flank pain who was subsequently found to have an incidental left adrenal mass on CT imaging. After appropriate diagnostic workup, the patient underwent surgical resection. A diagnosis of ES was made from the histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…There were only 3 cases of primary MRT and 4 cases of primary ES in the adrenal gland reported in the English literature (Table 1). [8][9][10][11][12][13][14] Only 1 of the 3 MRT cases occurred in a patient younger than 5 years. All 4 ES cases occurred in patients older than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…There were only 3 cases of primary MRT and 4 cases of primary ES in the adrenal gland reported in the English literature (Table 1). [8][9][10][11][12][13][14] Only 1 of the 3 MRT cases occurred in a patient younger than 5 years. All 4 ES cases occurred in patients older than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Of proximal ES arising from the adrenal gland, three out of four cases have been reported in female patients and occurred in the left adrenal gland [4][5][6]. Half of the adrenal cases had suspected lymph node involvement at resection [4][5][6]. In both instances, those with lymph node involvement had recurrence or progression of disease after surgical resection [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…SMARCB1/INI1 deficient proximal ES in adults have been documented in various gastrointestinal, genitourinary, neurological, and cutaneous locations [1,3]. However, very few cases in the literature have described these malignancies arising from the adrenal gland [4][5][6]. While a loss of SMARCBI/INI1 links these tumors, little is understood regarding other relationships [1].…”
Section: Introductionmentioning
confidence: 99%
“…During cycle 3, the disease progressed, and in spite of the treatment with tazemetostat, an activating enhancer of zeste homolog 2 (EZH2) inhibitor for ES, the patient died 2 months later after the therapy. Recently, Martinez et al ( 11 ) reported the third adrenal ES case in an 82-year-old female. The patient underwent extensive surgical excision.…”
Section: Discussionmentioning
confidence: 99%
“…The present study reported a rare case of proximal adrenal ES in a Chinese male adult. To the best of our knowledge, only 3 adult cases of this disease have been reported (9)(10)(11) and this is the first report of effective treatment with immune checkpoint inhibitors (ICIs) in advanced adrenal ES.…”
Section: Introductionmentioning
confidence: 99%